Some Problems of Food Safety in Georgia - Kbiladze, David; Metreveli, Shorena; Samsiani, Medea (Ekonomika, 2020)
The problem of production, export, import, and consumption of food was always topical for the long history of Georgia. At all stages of the society development, people need to take food and meet other of their elementary needs. Issues of food supply assurance of the Georgian population differ according to time periods. For example, in Shota Rustaveli’s poem The Knight in the Panther’s Skin it is described that the living standard in the 11th–13th centuries was quite high. At that period of time, Georgia was fed with its own grain. Along with wealth, Shota Rustaveli also characterizes poverty. Most of the state's income was spent on the poor people, so there was a large gap between the rich and poor population.In the 16th and 17th centuries, the problem of poverty and wealth of the population was highlighted by prominent public figures: Sulkhan – Saba Orbeliani and Vakhushti Bagrationi. Ilia Chavchavadze describes the problem of poverty in the country by the end of the 19th century. Poor living conditions of the population were noted during the initial phase of Georgia in Soviet Union and during World War II. Better conditions existed at the last stage of socialism.Meeting the population’s demand for principal foodstuffs and providing near-rational norms of such foodstuffs has always been a major objective of the governments of all times.The prolonged transformation process of the economy of Georgia with its social characteristics was particularly painful. A sharp decline in the standard of life started from the 1990s. Before the economic collapse, a monthly rated wage in Georgia with its foodstuff purchasing power parity almost equaled that of developed countries.
Keywords: food safety; indicators; production; export; import; consumption standards of products